Methodology for Investigation of Thermal and Physical Characteristics of Materials Having Special Properties - R. I. Esman; V. F. Shevtsov; G. B. Vasilkovski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes apparatus devices for investigation of heating processes and thermal and physical characteristics of composite materials using methods of contact, contactless thermometry, infra-red thermography and spectrophotometry.The developed measuring methods make it possible to investigate mechanisms and kinetics of radiation drying processes of multi-layer materials having special properties.